2008
DOI: 10.1111/j.1420-9101.2008.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and population structure of a New World predator, the army ant Eciton burchellii

Abstract: The army ant Eciton burchellii is probably the most important arthropod predator in the Neotropics, and many animal species depend upon it. Sex‐biased dispersal with winged males and permanently wingless queens may render this species especially sensitive to habitat fragmentation and natural barriers, which might have severe impacts on population structure and lead to population decline. Using nuclear microsatellite markers and mitochondrial sequences, we investigated genetic differentiation in a fragmented po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 62 publications
1
62
0
Order By: Relevance
“…A recent study showed that a Panamanian population of the army ant Eciton burchellii Mayr exhibits high nuclear gene flow, in spite of restricted maternal (mitochondrial) gene flow (Berghoff et al 2008). Obviously, male-mediated gene flow must be important in these ants.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that a Panamanian population of the army ant Eciton burchellii Mayr exhibits high nuclear gene flow, in spite of restricted maternal (mitochondrial) gene flow (Berghoff et al 2008). Obviously, male-mediated gene flow must be important in these ants.…”
Section: Introductionmentioning
confidence: 99%
“…This holds as well for the coxI barcoding fragments, while divergence becomes even more pronounced with 12.8 % on average between our Mexican lineages (14.2 % over all lineages). Though deep coxI divergence within some ant species seems not to be unusual (Smith et al 2005;Fisher and Smith 2008), and particularly in army ants restricted maternal dispersal may foster mtDNA differentiation (Berghoff et al 2008;Barth et al 2013), the inclusion of nuclear 28S fragments shows that our results are not an artifact of mtDNA divergence only. Taking the 28S phylogeny alone not only confirms the whole sequence tree topology but still results in a divergence of 3.7 % between colony Cac1 and the other three, compared to 0.0 % among the latter (2.4 % among all Labidus species).…”
Section: Discussionmentioning
confidence: 79%
“…The non-detection error of males (probability of genotypic identity by chance, Boomsma and Ratnieks 1996) is only 3.5 % for the two loci, and the nonsampling error is 0.53 on average, according to fitted Poisson distributions. Also population fragmentation can hardly explain this pattern because the well flying army ant males easily allow for gene flow within our sampling area (Berghoff et al 2008;Jaffé et al 2009;Barth et al 2013), and colonies Cac1 and Cac2 were even sampled in the very same time and place (Table 1). Thus, our results suggest two sympatric, but strongly reproductively isolated L. praedator lineages within our samples, which are, however, hardly distinguishable with the classical morphological keys (Borgmeier 1955;Watkins 1976Watkins , 1982 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A similar genetic population structure of the host plant and ant partner in the latter association suggested that the population structure reflected historical colonisation dynamics, underscoring the importance of interdependence among ant and plant partners in shaping the genetic population structure of both symbionts (Leotard et al, 2008). The highly specialised nesting requirements of obligatory social parasites that require host colonies of specific ant species for reproduction (Trontti et al, 2006) or specific breeding systems where one sex shows very limited dispersal only (Chapuisat et al, 1997;Doums et al, 2002;Oberstadt & Heinze, 2003;Berghoff et al, 2008) have also been discussed as a factor responsible for strong differentiation at small spatial scales.…”
Section: Discussionmentioning
confidence: 99%